Biochemical status of blood of dogs with atopic dermatitis in the conditions of private veterinary clinic “Alfa vet” m. Konotop - Olga Stotska (Scientific Route OÜ, 2021)
Metabolic changes in the body of dogs with atopic dermatitis and the causes of its occurrence still remain poorly understood. This study confirms the need for biochemical blood tests for the differential diagnosis of skin diseases in animals.